Effect of Subject Rotation on Assessment of Esthetic Dental Ratios: A Simulation Study - Gyawali, Rajesh (Int J Dent, 2016)
Objective. This study aimed to find out the change in esthetic ratios during rotation of patient's head using a simulation. Materials and Methods. A plaster study model was photographed placing its midline along the long axis of the camera. Then a series of photographs were taken by rotating the model each degree till 10° on both right and left sides. These photographs were digitally measured and the ratio of the maxillary anterior teeth at zero-degree rotation was compared with that at various degrees of rotation. Results. As the model was rotated to the right side till 10°, the ratio of the right lateral to central incisor gradually decreased while the ratio of the left lateral to central incisor gradually increased. However, the ratio of the canine to lateral incisor on both sides gradually increased. Similar results were obtained when the model was rotated to the left side. The ratio of the lateral to central incisor deviated from the acceptable range (±10%) when there was rotation of more than 7°, whereas the ratio of the canine to lateral incisor was within the acceptable range till 10° rotation on either side. Conclusions. Rotation of the model by more than 7° leads to a substantial change in the esthetic ratio.